(untitled) (UNED Research Journal, 2019)
Introduction: Joturus pichardi is an important migratory species that inhabits the rivers of the Atlantic zone of Costa Rica and has been little studied. Objective: To describe the diet and reproduction of J. pichardi and its relationship with environmental factors in the Pacuare River basin. Methods: Sixteen sampling sites were selected along the main channel or Pacuare River. The samplings were performed from October 2015 to October 2016. The gonads, stomach, and intestines of seven individuals of J. pichardi were analyzed. The relationship of J. pichardi between the physicochemical variables of the water and the structure of the habitat was analyzed. Results: Twenty individuals were collected at an elevation of 225-235masl. The occurrence of J. pichardi was related to sites with higher river velocity, high values of dissolved oxygen, rock substrate and forest land use. All the individuals analyzed had visceral fat and endoparasites in the stomach. Bryophytes, ferns, macroinvertebrates, and detritus were identified as part of the diet of J. pichardi. According to the analysis of gonads in adults, the individuals were identified in the gonadal state types I, II and V. Conclusions: Our results suggest J. pichardi is an omnivorous species associated with sites with rocks, rapids, well-oxygenated waters, and forest land use. Also, the analysis of gonads coincides with the known reproduction period of the species. Finally, individuals of Neoechinorhynchus spp. are recorded for the first time in stomachs of J. pichardi in Costa Rica.